Densités des offres scolaires locales et politiques scolaires localisées - Guillaume Dupuy (Nantes Université, 2015)
This article shows the very different and large range of local school offers and their impact on school policies. Strict strategies are all the more difficult to undertake that they are contrary to the interests of the elected representatives of the concerned areas and contrary to some state-employed teachers or officials. And whereas the numerous school offers lead to strict strategies, the consequences of shortage situations are contrasted in state schools and private schools. If the bulding of state secondary schools is easily agreed, there is nearly no pratical possibility to create new private secondary schools; and this gradually implies that private schools tend to be more selective from an academic and social point of view, and to be located in the most attractive school aeras.